Animal Spirits, Financial Crises and Persistent Unemployment*. (26th April 2013) - Farmer, Roger E.A.
<x xml:space="preserve">Abstract</x> This article uses a rational expectations model with multiple equilibrium unemployment rates to explain financial crises. The model has equilibria where asset prices are unbounded above. I argue that this is an important feature of any rational‐agent explanation of a financial crisis, since for the expansion phase of the crisis to be rational, investors must credibly believe that asset prices could keep increasing forever with positive probability. I explain the sudden crash in asset prices that precipitates a financial crisis as a large shock to expectations that leads to a permanent increase in the unemployment rate.